Carboxylated Magnetite Composite Polymer Nanoparticles with Mosaic Structure for Biomedical Application - Sykam, Kesavarao; Donempudi, Shailaja (Journal of Research Updates in Polymer Science, 2015)
In this article, a microemulsion method for preparation of magnetite composite polymer nanoparticles of Fe3O4@poly(styrene-methacrylic acid) (MNP@PSMA) crosslinked with1,6-hexanediol diacrylate (HDD) insitu with carboxyl functionality on the surface has been reported. Structure and morphology of the nanoparticles was studied by Fourier Transform Infrared spctroscopy (FTIR), X ray Diffraction (XRD), Thermal Gravimetric Analyser (TGA), Vibrating Sample Magnetometer (VSM) and Transmission Electron Microscopy (TEM). VSM studies confirmed saturation magnetization of 20.0 emu/g in an external magnetic field. Nanoparticles formed were of 30 nm in diameter with narrow size distribution and mosaic structure providing a large surface area useful for application in bioseparation. Experimental results of covalent coupling of composite nanoparticles indicated maximum protein binding capacity of 350 mg bovine serum albumin (BSA) per gram.